2018
DOI: 10.1007/s00439-018-1928-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability

Abstract: Identification of Mendelian genes for neurodevelopmental disorders using exome sequencing to study autosomal recessive (AR) consanguineous pedigrees has been highly successful. To identify causal variants for syndromic and non-syndromic intellectual disability (ID), exome sequencing was performed using DNA samples from 22 consanguineous Pakistani families with ARID, of which 21 have additional phenotypes including microcephaly. To aid in variant identification, homozygosity mapping and linkage analysis were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 94 publications
(108 reference statements)
0
43
0
1
Order By: Relevance
“…Five cases in three distinct families had bi-allelic variants, consistent with autosomal recessive inheritance (Table 1; Figure 1). Two of these individuals were compound heterozygotes, whereas the other three were siblings from a consanguineous family homozygous for the same variant (Table 1; Figure 1) 22 . In all three of the autosomal recessive families, at least one parent appeared mildly affected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five cases in three distinct families had bi-allelic variants, consistent with autosomal recessive inheritance (Table 1; Figure 1). Two of these individuals were compound heterozygotes, whereas the other three were siblings from a consanguineous family homozygous for the same variant (Table 1; Figure 1) 22 . In all three of the autosomal recessive families, at least one parent appeared mildly affected.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals 3-I, 3-II, and 3-III were consented for research-based exome sequencing as described 22 , and individuals 7-I and 7-II were consented for research-based trio exome sequencing through the Deciphering Developmental Disorders (DDD) study 35 .…”
Section: Human Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, Johansen et al (2016) reported for the first time 16 patients from six different consanguineous families harboring homozygous inactivating variants in the MBOAT7 gene (OMIM 606048). Since then, other 27 patients with MBOAT7 defects were identified (Hu et al, 2019; Jacher, Roy, Ghaziuddin, & Innis, 2019; Khan et al, 2019; Santos‐Cortez et al, 2018; Yalnızoǧlu et al, 2019). As summarized by Khan et al (2019), 13 different MBOAT7 variants in 18 families have been described until now, of which 5 are frameshift mutations, 2 are splice, 1 is nonsense, 3 are missense, 1 is a 21 bp in frame deletion, 1 is a 11,549 bp deletion.…”
Section: Introductionmentioning
confidence: 99%